Strangely familiar: The surprise ending in Poe, Maupassant, and Borges - Abou Senna, Pacinthe Adel (AUC Knowledge Fountain, 2016)
This thesis mainly explores the surprise ending and how it creates different reactions from the audience. The particular stories I chose for Poe, Maupassant and Borges can all be categorized under the fantastic genre. These tales offer different perspectives of the unconscious, particularly the uncanny, through their main characters. In Poe’s short stories, “The Tell-Tale Heart” and “William Wilson,” the protagonists are haunted and tormented by their doubles, forcing them to behave frantically. The Maupassant short stories, La Nuit” (Night) and “Sur l’ Eau” (On the River), mainly revolve around the theme of loneliness, where the narrators attempt to escape their terrifying situations on their own. As for the Borgesian tales, “La Casa de Asterión” (The House of Asterion) and “Abenjacán el Bojarí, muerto en su laberinto” (Ibn-Hakam al-Bokhari, Murdered in His Labyrinth), they mainly highlight the theme of the labyrinth. While reading, I empathize with the protagonists’ horrifying accounts, experiencing contradictory feelings of pleasure and fear. However, knowing that I am safely on the other side of the book, I immerse myself into these stories’ insight of a relatively unknown and obscure territory: the unconscious. In most of these tales, specifically at the climax, the events take a sudden shift towards the solution of the mystery, resulting in a modern “peripeteia,” the surprise ending. Some would consider this resolution as reducing the mystery into disappointing, mundane logic. On the other hand, this ending might bring relief, allowing the readers to be cathartically satisfied. In this comparative study, I investigate these narratives of the uncanny and the sublime experience they offer to the reader through some of the ideas of Aristotle, Tzvetan Todorov, Immanuel Kant, and Sigmund Freud. I also examine how these tales’ effects are challenged by the surprise ending that denies the audience from finding truth and entraps them in a repetition compulsion.